The Role and Significance of Organization of Islamic Cooperation (OIC) in Global Issues: A Case Study of Islamophobia in France: Indonesia - Andreas Hari Kristiyanto; Putri Andjani Nur Afifah; Siti Rahmah (Universitas Muhammadiyah Malang, 2024)
The Organization of Islamic Cooperation (OIC) plays a significant role in addressing global issues such as the case study discussed in this research regarding Islamophobia in France. This study analyzes the role and significance of the OIC in tackling this issue using a qualitative literature research method by drawing upon sources from previous studies. By employing international organization theory, it can be concluded that the OIC can act as an extension of states in responding to global issues, in this case, Islamophobia in France, by assuming roles as an initiator, mediator, and facilitator. This study provides a more nuanced understanding of the efforts made by the OIC in addressing complex and sensitive global issues such as Islamophobia in France.